OP0034 Efficacy and Safety of Mavrilimumab, A Fully Human Gm–CSFR-Alpha Monoclonal Antibody in Patients with Rheumatoid Arthritis: Primary Results from the Earth Explorer 1 Study. (9th June 2015) - Burmester, G.R.; McInnes, I.B.; Kremer, J.M.; Miranda, P.; Korkosz, M.; Vencovsky, J.; Rubbert-Roth, A.; Mysler, E.; Sleeman, M.A.; Godwood, A.; Albulescu, M.; Close, D.; et al.
Abstract : Background: Of patients with RA, ∼40% of do not achieve a minimal acceptable improvement (ACR20) despite modern biologic therapy. 1, 2, 3 Granulocyte-macrophage colony-stimulating factor (GM–CSF) is implicated in RA pathogenesis via myeloid and granulocyte cell lineage activation. In a 12-week Phase IIa study, mavrilimumab, a first-in-class inhibitor of the GM–CSF receptor-α demonstrated a sustained effect via this novel therapeutic pathway in RA. 4 Objectives: To evaluate the efficacy and safety of mavrilimumab in patients with moderate to severe, adult-onset RA in a 24-week, Phase IIb study. Methods: Patients (18–80 yrs; inadequate response to ≥1 DMARDs; DAS28–CRP ≥3.2; ≥4 SJC) receiving MTX were randomized to receive 1 of 3 SC mavrilimumab dosages (150, 100, 30 mg every other week [eow]) or placebo (PBO) plus MTX (7.5–25.0 mg/week). Co-primary endpoints were change in DAS28–CRP (Day 1 to Week 12) and ACR20 response rate (Week 24). Safety and tolerability were measured through assessment of AEs and pulmonary parameters. Results were analyzed using the modified ITT population. Results: 326 patients from Europe, South America, and South Africa (mean [SD] age, 51.8 [11.1] yrs; female, 86.5%; mean [SD] DAS28–CRP, 5.8 [0.9]; RF+/anti-CCP+, 81.9%) received mavrilimumab 150, 100 or 30 mg eow or PBO (N=79, 85, 81 and 81, respectively). At Week 12, a statistically significant difference in DAS28–CRP change from baseline ( p <0.001) was observed for all dosages of mavrilimumab vs. PBO. At Week 24, a significantly greater percentage of all mavrilimumab-treated patients also met the ACR20 co-primary endpoint vs. PBO (table ). A dosage response was observed across several secondary endpoints, with separation from PBO evident as early as Week 1 and first dose. The most common treatment-emergent AEs were headache (7.6%, 4.7%, 6.2%, 2.5%), nasopharyngitis (7.6%, 3.5%, 4.9%, 7.4%) and bronchitis (5.1%, 1.2%, 3.7%, 7.4%) for mavrilimumab 150, 100, 30 mg eow or PBO, respectively. There was no increase in pulmonary AEs for mavrilimumab vs. PBO (6.3%, 3.5%, 6.2% vs. 9.9%). No serious infections were observed in the 100 and 150 mg eow groups. Two cases of pneumonia were observed (one each in mavrilimumab 30 mg eow and PBO groups). There were no deaths or anaphylaxis, and no apparent dosage relationship for AEs. >90% of patients entered a long-term, open-label extension study. Conclusions: This Phase IIb study demonstrated the potential benefit of inhibiting macrophage activity via the GM–CSF receptor-α pathway on RA disease activity. The study met both co-primary endpoints with a clear dosage response. Mavrilimumb was well-tolerated over the 24-week study period. References: Weinblatt ME, et al. N Engl J Med 1999;340:253–9. Lipsky PE, et al. N Engl J Med 2000;343:1594–602. Weinblatt ME, et al. Arthritis Rheum 2003;48:35–45, Burmester GR, et al. Ann Rheum Dis 2013;72:1445–52. Acknowledgements: Funded: MedImmune. Editorial assistance: N Panagiotaki, QXV Communications, UK † Joint senior authors. Disclosure of Interest: G. Burmester Grant/research support from: AbbVie, Pfizer, UCB, Roche, Consultant for: AbbVie, BMS, Novartis, MedImmune, MSD, Pfizer, UCB, Roche, Speakers bureau: AbbVie, BMS, Novartis, MSD, Pfizer, UCB, Roche, I. McInnes Grant/research support from: MedImmune (Research award to University of Glasgow), Consultant for: MedImmune, AstraZeneca, J. Kremer Shareholder of: Corrona, Grant/research support from: AbbVie, Amgen, Genentech, Lilly, Pfizer, Consultant for: AbbVie, Amgen, Genentech, Lilly, Pfizer, BMS, Employee of: Corrona, P. Miranda Grant/research support from: MedImmune (to support protocol), M. Korkosz: None declared, J. Vencovsky: None declared, A. Rubbert-Roth Grant/research support from: Pfizer, Chugai, Consultant for: MSD, USB, Abbott, Pfizer, Roche, BMS, Chugai, Speakers bureau: Roche, Pfizer, UCB, E. Mysler Grant/research support from: Medimmune, Roche, BMS, Pfizer, M. Sleeman Shareholder of: AstraZeneca, Employee of: MedImmune, A. Godwood Shareholder of: AstraZeneca, Employee of: MedImmune, M. Albulescu Employee of: MedImmune, D. Close Shareholder of: AstraZeneca, Employee of: MedImmune, M. Weinblatt Grant/research support from: BMS, UCB, Crescendo Bioscience, Consultant for: MedImmune, AstraZeneca, Amgen, Abbvie, BMS, Crescendo Bioscience, Lilly, Pfizer, UCB, Roche